Educação e urbanidade indígena : nas fronteiras xavantinenses - Serpa, Aila Oliveira (2017)
This work aims to understand how the presence of A‟uwe (Xavante) is perceived by the managers and teachers of a public state high school in Nova Xavantina-MT; investigate if this school thinks and recognizes the paper that the school education has in the formation of the Xavante, if the teachers know the law 11.645/08, if they are prepared to execute in an intercultural perspective that recognize the cultural necessities of this people and if, prepared or not, they seek to adapt their practices to include this thematic in the daily school life. Part of the conception that is important that the new studies search to understand the indigenous in the city, escaping from the limiting dichotomies in this comprehension, and promoting the dialogue between the worlds and their cultures in contact in school. Culture, otherness, identity and interculturality were the main concepts to the comprehension of the interethnic relations and formation of the frontiers in which these relations take place. The research of Ethnographic type was used as a basis for data collection and its interpretation. The data demonstrate the city of Nova Xavantina and the school focus of the research like spaces of frontier where the interethnic friction occurs, in which the contradictions are manifested in tensions and conflicts symptomatic in the high rate of evasion and school disapproval of indigenous students. We understand that the school should represent the possibility of learning to connect with surround society without losing or disqualifying its own culture; which, unfortunately, it was not verified in the case studied. The cultural and historical diversity of the Indigenous Peoples of Brazil is huge, like is also huge the diversity that manifests the indigenous presence in the city demonstrating that there is not a situation of urbanity, but several and that each case, each specificity implies in a way to relate to it. Thereby, considering the case of insertion of the Xavante in Nova Xavantina, we take place its socio-cosmology, which must also be done by the school that receives these students. On the questions about diversity we can note that the analytic key and the inclusion practice are almost exclusively of the people with special needs, it is dominant; so aspects considered innovative, such the law 11.645/08 and the intercultural education are widely unknown, or only mentioned, and with the referential documents from school that bring, they need knowledge and didactics sources to be taken to the classroom. Understanding the process of thinking about oneself, about what the school is and want to be that is part of the school culture studied, it is only that this subject being added to the thematic of diversities, the theoretical basis, the subsidies that lead to the comprehension of fundamental concepts to the formation of and in practice. Finally, we understand that is like this that a new educational system based in the interculturality and of pluri-ethnicity can be realized.